2018
DOI: 10.26722/rpmi.2017.24.71
|View full text |Cite
|
Sign up to set email alerts
|

Determinacion estructural de flavonoides en el extracto etanolico de cladodios de Opuntia ficus-indica (L.) Mill. Tuna Verde

Abstract: Objetivos. Determinar estructuralmente los flavonoides encontrados en el extracto etanolico de cladodios de Opuntia ficus-indica (L.) Mill. Tuna verde. Materiales y Métodos. Se preparo el extracto etanolico de cladodios de Opuntia ficus-indica (L.) Mill. Luego, se detectaron sus componentes mediante un tamizaje fitoqui­mico. A traves de cromatografia en capa fina se aislaron los compuestos fenolicos tipo flavonoides. Finalmente, usando espectroscopia UV/Vis se propuso la posible estructura de los flavonoides e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Rivera (2019) and Haratym (2017) reported the presence of alkaloids, saponins, and various groups of phenolic compounds in Marrubium vulgare L leaves. 25,26 Furthermore, Tripathi (2017) and Njinga (2020) identified alkaloids in different plants belonging to the Lamiaceae family, such as Mentha piperita, Ocimum tenuiflorum, and Ocimum gratissimum Linn. 27,28 Total Alkaloid Yield Extraction results are illustrated in Figure 1.…”
Section: Alkaloids Detectionmentioning
confidence: 99%
“…Rivera (2019) and Haratym (2017) reported the presence of alkaloids, saponins, and various groups of phenolic compounds in Marrubium vulgare L leaves. 25,26 Furthermore, Tripathi (2017) and Njinga (2020) identified alkaloids in different plants belonging to the Lamiaceae family, such as Mentha piperita, Ocimum tenuiflorum, and Ocimum gratissimum Linn. 27,28 Total Alkaloid Yield Extraction results are illustrated in Figure 1.…”
Section: Alkaloids Detectionmentioning
confidence: 99%
“…Another study carried out by column chromatography, showed that a combination of 45℃ and airflow allowed optimal preservation of phenols and flavonoids (Medina-Torres et al, 2011). The cladodes extracted by ethanol exhibited good solubility in polar solvents because the polar compounds act as scavengers against reactive oxygen species (Bonilla Rivera et al, 2017). Lastly, the Soxhlet and maceration method conducted by Ammar et al (2015) in which variability in the extracts yields was attributed to the different polarities of the solvents used; in particular, the methanol and water extract produced the highest extraction yields.…”
Section: Extraction Techniques For the Analysis And Characterization Of Polyphenolsmentioning
confidence: 99%